The Economic Law of Market Areas - Hyson, C. D.; Hyson, W. P. (Quarterly Journal of Economics, 1950)
Journal Article The Economic Law of Market Areas Get access C. D. Hyson, C. D. Hyson Oslo, Norway Search for other works by this author on: Oxford Academic Google Scholar W. P. Hyson W. P. Hyson Oslo, Norway Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 64, Issue 2, May 1950, Pages 319–327, https://doi.org/10.2307/1882699 Published: 01 May 1950